PENERAPAN ASAS KEBEBASAN BERKONTRAK DALAM PEMBUATAN PERJANJIAN FRANCHISE ES TELER 77 (Suatu Pendekatan Normatif) - Ery Agus Priyono (Faculty of Law, Universitas Diponegoro, 2015)
Traditionally, a contract performs based on the result of prior negotiation between the parties, who have an equal bargaining position. Recently the trend shows many businessmen doing their businesses did not base on equal business negotiation, cause of unequal bargaining position but one party already set forth standard requirements in an agreement form, then offers to the other party. The research problem which come up; are the standard requirements in standard contract or agreement not in contrary with Freedom of Contract principle. The research result shows, stronger party (Franchisor) breached the Freedom of Contract, and consensual principles In contrary many clauses set franchisor rights with a less obligations. Based on the literary study judge has rights to omit the clauses which strongly potential to give disadvantages to one party and give advantages to the other partySecara tradisional suatu perjanjian terjadi berlandaskan asas kebebasam berkontrak di mana dua pihak yang mempunyai kedudukan yang seimbang berusaha untuk mencapai suatu kesepakatan yang diperlukan bagi terjadinya perjanjian itu melalui suatu proses negosiasi diantara mereka. Namun pada dewasa ini kecenderungan makin nyata bahwa banyak perjanjian di dalam transaksi bisnis yang terjadi bukan melaui proses negosiasi yang seimbang di antara para pihak, tetapi perjanjian itu terjadi dengan cara pihak yang satu telah menyiapkan syarat-syarat baku pada suatu formulir perjanjian yang sudah dicetak dan kemudian disodorkan kepada pihak lainnya untuk disetujui. Permasalahan yang muncul adalah apakah perjanjian baku yang dibuat oleh para pebisnis tidak bertentangan dengan asas kebebasan berkontrak, Hasil penelitian menunjukkan telah terjadi pelanggaran terhadap asas kebebasan berkontrak